Autosomal recessive variants c.953A>C and c.97-1G>C in NSUN2 causing intellectual disability: a molecular dynamics simulation study of loss-of-function mechanisms - Muhammad, Nazif; Hussain, Syeda Iqra; Rehman, Zia Ur; Khan, Sher Alam; Jan, Samin; Khan, Niamatullah; Muzammal, Muhammad; Abbasi, Sumra Wajid; Kakar, Naseebullah; Rehman, Zia Ur; Khan, Muzammil Ahmad; Mirza, Muhammad Usman; et al. (Frontiers in Neurology, 2023)
Introduction Intellectual disability (ID) is a clinically and genetically heterogeneous disorder. It drastically affects the learning capabilities of patients and eventually reduces their IQ level below 70. Methods The current genetic study ascertained two consanguineous Pakistani families suffering from autosomal recessive intellectual developmental disorder-5 (MRT5). We have used exome sequencing followed by Sanger sequencing to identify the disease-causing variants. Results and discussion Genetic analysis using whole exome sequencing in these families identified two novel mutations in the NSUN2 (NM_017755.5). Family-A segregated a novel missense variant c.953A>C; p.Tyr318Ser in exon-9 of the NSUN2. The variant substituted an amino acid Tyr318, highly conserved among different animal species and located in the functional domain of NSUN2 known as “SAM-dependent methyltransferase RsmB/NOP2-type”. Whereas in family B, we identified a novel splice site variant c.97-1G>C that affects the splice acceptor site of NSUN2. The identified splice variant (c.97-1G>C) was predicted to result in the skipping of exon-2, which would lead to a frameshift followed by a premature stop codon (p. His86Profs*16). Furthermore, it could result in the termination of translation and synthesis of dysfunctional protein, most likely leading to nonsense-mediated decay. The dynamic consequences of NSUN2 missense variant was further explored together with wildtype through molecular dynamic simulations, which uncovered the disruption of NSUN2 function due to a gain in structural flexibility. The present molecular genetic study further extends the mutational spectrum of NSUN2 to be involved in ID and its genetic heterogeneity in the Pakistani population.